11 A multi-physics approach enabling rare cell isolation with high recovery and high purity. (10th December 2020) - Yu, Liping; Sa, Silin; Wang, Alice
Abstract : Background: Advancements in fields of multi-omics analysis and cell-based therapies depend upon efficient cell processing tools to isolate rare cancer and immune cells from complex biologic samples as an initial step in sample preparation. Conventional technologies are limited in automation, recovery and purity. We present an integrated system based on multiple physics principles with built-in novel technologies to achieve cell purification, concentration and target cell isolation, with high recovery at an unprecedented flow rate. This platform, the Multi-physics Automated Reconfigurable Separation (MARS), combines tunable, acoustic cell processing and in-flow immuno-magnetic separation technologies, enabling automation of the entire cell sample preparation workflow for proteomics and genomics analysis. Methods: Circulating tumor cells (CTC) are present in extreme low frequency in blood stream (1–100 in billions of blood cells) thus it has been a challenge to isolate CTCs with high recovery. We have developed protocols on MARS to isolate CTCs from whole blood for multi-color flow cytometry analysis. To demonstrate the extent of enrichment of tumor cells in whole blood, PC3 cells were used for spike recovery. RBC lysed blood sample was then loaded on MARS and automatically processed through cell washing, concentration, and magnetic depletion. Enriched tumor cells were collected and analyzed by flow cytometry. Results: Results show > 4 log enrichment of tumor cells and average recovery of spiked CTC > 85% in the clinical relative range <100 cells per ml of whole blood (R2=0.929) with a throughput of 60 ml/hr. Isolated cells were confirmed to be cancer cells with imaging analysis and single cell genomic sequencing. The protocol was also validated with other cell line cells such as A549. The purity of the cells prepared by MARS are ideal for single cell genomics platforms. Conclusions: The fluidics of MARS is also replaceable and can be sterilized to minimize sample to sample contamination. The high molecular debris removal achieved by MARS is ideal for single cell genomics platforms, as is the first-to-market automated and integrated sample preparation and cell separation system designed to be a versatile tool for downstream cell analysis.